PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Nugraha Farelio Siregar; Nila Firdausi Nuzula (Jurnal Administrasi Bisnis, 2020)
Corporate governance is a set of systems and rules governing corporate organs and stakeholders in the context of rights and obligations. One of the objectives of implementing corporate governance is to create and add value to stakeholders in the long term. Corporate governance can increase firm value by increasing investor confidence in improving performance and reducing the risk of fraud. Investors prefer companies that have good corporate governance. Aside from corporate governance, the firm value can also be influenced by the profitability of the company. The reason is that investors are more interested in companies that have high profitability. This study aims to determine the influence of corporate governance which is proxied by the Proportion of Independent Board of Commissioners (X1), Board of Directors (X2), Audit Committee (X3), Managerial Ownership (X4) and profitability which is proxied by Return on Assets (X5), Return on Equity (X6) as an independent variable on firm value (Y) as measured by Tobin's Q. This type of research is an explanatory research with a quantitative approach. This research was conducted on 16 samples of mining companies listed on the Indonesia Stock Exchange on period 2016-2018. Samples were obtained through purposive sampling method. The analysis technique is used multiple linear regression. Keywords : Proportion of Independent Board of Commissioners, Board of Directors, Audit Committee, Managerial Ownership, Return on Assets, Return on Equity, Firm Value